Multi-institutional validation of the ESMO-ESGO-ESTRO consensus conference risk grouping in Turkish endometrial cancer patients treated with comprehensive surgical staging. (3rd April 2021) - Gultekin, Melis; Guler, Ozan Cem; Yuce Sari, Sezin; Akkus Yildirim, Berna; Onal, Cem; Celik, Husnu; Yuce, Kunter; Ayhan, Ali; Arik, Zafer; Kose, Fatih; Altundag, Ozden; Zoto Mustafayev, Teuta; et al.
Abstract: In this study, 683 patients with endometrial cancer (EC) after comprehensive surgical staging were classified into four risk groups as low (LR), intermediate (IR), high-intermediate (HIR) and high-risk (HR), according to the recent consensus risk grouping. Patients with disease confined to the uterus, ≥50% myometrial invasion (MI) and/or grade 3 histology were treated with vaginal brachytherapy (VBT). Patients with stage II disease, positive/close surgical margins or extra-uterine extension were treated with external beam radiotherapy (EBRT)±VBT. The median follow-up was 56 months. The overall survival (OS) was significantly different between LR and HR groups, and there was a trend between LR and HIR groups. Relapse-free survival (RFS) was significantly different between LR and HIR, LR and HR and IR and HR groups. There was no significant difference in OS and RFS rates between the HIR and HR groups. In HR patients, the OS and RFS rates were significantly higher in stage IB – grade 3 and stage II compared to stage III and non-endometrioid histology without any difference between the two uterine-confined stages and between stage III and non-endometrioid histology. The current risk grouping does not clearly discriminate the HIR and IR groups. In patients with comprehensive surgical staging, a further risk grouping is needed to distinguish the real HR group. Impact statement: What is already known on this subject? The standard treatment for endometrial cancer (EC) is surgery and adjuvant radiotherapy (RT) and/or chemotherapy is recommended according to risk factors. The recent European Society for Medical Oncology (ESMO), European Society of Gynaecological Oncology (ESGO) and European Society for Radiotherapy and Oncology (ESTRO) guideline have introduced a new risk group. However, the risk grouping is still quite heterogeneous. What do the results of this study add? This study demonstrated that the current risk grouping recommended by ESMO-ESGO-ESTRO does not clearly discriminate the intermediate risk (IR) and high-intermediate risk (HIR) groups. What are the implications of these findings for clinical practice and/or further research? Based on the results of this study, a new risk grouping can be made to discriminate HIR and IR groups clearly in patients with comprehensive surgical staging.